1980
DOI: 10.1111/j.1432-1033.1980.tb04498.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Glucose to Dolichyl Diphosphate Oligosaccharide and Transfer to Protein

Abstract: The glycosylation of asparagine residues in proteins is known to occur by transfer from a dolichyl diphosphate oligosaccharide containing glucose. Paper chromatography allowed the separation of oligosaccharides (obtained by acid hydrolysis of the dolichyl diphosphate derivative) containing 1, 2 and 3 glucose residues. Using this procedure it was found that the addition of all three glucoses to the dolichyl diphosphate oligosaccharide occur with dolichyl phosphate glucose as donor. Furthermore only the compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…The three terminal glucose residues of the lipid-linked core oligosaccharide have been shown to be important determinants for substrate affinity to the oligosaccharyltransferase in vitro (4,(6)(7)(8)(9)(10). In vivo, the three yeast mutants accumulating Man9GlcNAc2 (aigS, alg6, and dpgl) and alg8 (accumulating Glc1Man9GlcNAc2) were found to underglycosylate secreted invertase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three terminal glucose residues of the lipid-linked core oligosaccharide have been shown to be important determinants for substrate affinity to the oligosaccharyltransferase in vitro (4,(6)(7)(8)(9)(10). In vivo, the three yeast mutants accumulating Man9GlcNAc2 (aigS, alg6, and dpgl) and alg8 (accumulating Glc1Man9GlcNAc2) were found to underglycosylate secreted invertase.…”
Section: Discussionmentioning
confidence: 99%
“…Glc3Man9GlcNAc2 is the preferred substrate ofthe oligosaccharyltransferase. Removal of one, two, or all three glucose residues drastically reduces the transfer rate of the lipid-linked oligosaccharide to protein in vitro (4,(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, essentially two possible functions of the transient methylation of the dolichyMinked oligosaccharides are conceivable: since dolichol derivatives do not translocate spontaneously across the lipid bilayer [41] the methylation could represent an obligatory step for translocation of the lipid oligosaccharide. Alternatively, the 3-O-methylglucose could serve a function similar to that attributed to the glucose residues on the lipid-linked Glc 3 Man 5 GlcNac 2 or GlclMan s GlcNac 2 [42,43] involved in eucaryotic glycoprotein synthesis, namely to facilitate the transfer of the oligosaccharide to protein [44][45][46][47][48][49][50][51]. It is not known whether the 3-O-methylglucose residue is removed from the oligosaccharide at the lipid-linked level or at the protein-linked level.…”
Section: Biosynthesis Of Sulfated Oligosaccharidesmentioning
confidence: 99%
“…It has become evident in recent years that glycosylation of asparagine residues in eukaryotic cell proteins involves dolichol pyrophosphate (DolPP)-bound oligosaccharides as intermediates (1). It has been reported that in animal tissues (2,3), yeasts (4)(5)(6), and probably also in insects (7) and plants (8), the oligosaccharide transferred from the lipid derivative to proteins is composed of two N-acetylglucosamine, nine mannose, and three glucose residues. A report by Lehle suggests that in yeast the oligosaccharides containing two or three glucose residues are equally transferred to protein (9).…”
mentioning
confidence: 99%